Livelihood Strategy of Tempo Driving as a Livelihood Strategy in Bhojpur Municipality, Bhojpur - Rai, Saran Kumar (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2025)
Livelihood strategy is the dynamic and complex phenomena. It is changing over space and time. This paper examines the socio-economic condition and livelihood strategy of tempo drivers in Bhojpur Municipality.There are emerging tempo drivers day by day due to available of road network in Bhojpur Municipality. This study completely based on primary and secondary data and it follows descriptive research design and qualitative approach. This paper focuses mainly on tempo drivers’ socio-economic status and their livelihood strategy. Tempo driving is the most important for the local people to travel from one place to another place. It is the responsibility of local government to make effective and better management of the tempo driving for the sustainable development of rural livelihood. Tempo driving is one of the ways of the employment and livelihood strategy where unemployment changed into employment. Likewise other local people got the facility to travel from one place to another place.